Macroeconomic policies and industrial wood processing and trade in Zimbabwe - Kowero, G.S.; Mabugu, R. (2005)
The purpose of this paper is to investigate the association between macroeconomic policies and industrial forestry developments in Zimbabwe. A principal rationale for the emphasis on macroeconomic aspects is that the macroeconomy provides underlying factors in forestry development. The paper demonstrates that: (a) macroeconomic policies promoted some industrial forestry activities in the post-independence period, more during the economic structural adjustment programme (ESAP) era when there were more pro-export policies, and then less in the recent post-ESAP years when dirigisme returned and the economy almost collapsed; (b) economic reform policies which initially had the greatest impact on industrial forestry were those of trade liberalisation and domestic deregulation, which came at a time when world timber markets were strengthening and therefore provided the timber industry with the capacity to grow, develop a wide range of products and adopt an export focus; (c) timber production for construction tends to increase with economic growth and vice versa; (d) in the post-ESAP period the forest industry has been characterised by uncertainty of tenure for its plantations due to recent changes in land laws, high inflation that erodes profitability, local market shrinkage due to prevailing stressed economy, loss of investor confidence and unrealistic currency exchange rates that make exporting unattractive. All these combine to form a very hostile environment for the forestry industry.